(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless Sensor Networks (WSN) can be defined as a self configured network formed using a large numbers of sensor nodes distributed over a geographical area with either predefined location or randomly deployed. Individual sensor nodes posses limited processing, communicating and energy recourses. These sensor nodes can sense, measure, and gather information from the vicinity, based on the local pre defined decision process, can transmit the sensed information (data) to the user or information sink. Communication of sensed data from the sensor nodes to information sink happens to be the main cause of energy depletion in sensor nodes. In order to extend the active life of WSN, it is required to process data locally and send the processed information to sink node. One of possible solution for optimal use of available energy is by using cluster based routing protocols